Membangun Citra Merek Melalui Fotografi Produk Sepatu Bagi UMKM Di Mojokerto - Rizky Pratama Ramadhani; Dhani Ichsanuddin Nur (Jurnal Informasi Pengabdian Masyarakat, 2023)
Technological advances are increasingly having a major impact on human daily life, one of which has an impact on UMKM. With the internet, the term digital marketing through social media can be born to increase brand awareness, build brand image and retain customers. For this reason, photography and social media content creation are needed in promoting on social media following the developing trend. Content creation can be done in simple ways and tools without expensive equipment. By using the method of discussion, interview, and direct practice using the help application in the form of an open camera along with how to adjust it and other supporting properties to enrich the appearance of the product to be more attractive. With this socialization and training, it can help UMKM in conducting independent promotions without the need for third party assistance.